Dynamical Properties of a Herbivore-Plankton Impulsive Semidynamic System with Eating Behavior - Yufei Wang; Huidong Cheng; Qingjian Li (Complexity)
In this paper, an impulsive semidynamic system of the relationship between plankton and herbivore is established, and the Poincaré map method is used to extend the new properties of the model. We define the Poincaré map of the impulsive point series in phase concentration and analyze the characteristics. A comprehensive and detailed analysis of the periodic solution is performed. In addition, the numerical simulations illustrate the correctness of our arguments. The results show that plankton and herbivore can survive stably under effective control.